Worth a thousand words: the impact of images on the perception of pollinator habitat - Jackman, Sarah M. (Kansas State University, 2018)
The pollinator crisis - a catastrophic decline in domestic and feral pollinator populations across the world - has grown in severity over the last decade, and recent rise in the publicity of pollinator decline has brought it to the forefront of conservation work. The decline in pollinator populations is due to many human and environmental factors – one of the most prominent being the decline in natural pollinator habitat as urban and agricultural areas expand. Designed urban pollinator habitat can fill the need for foraging and shelter, however gaining public support for these ecological spaces can be a difficult endeavor. Pollinator gardens and urban ecological habitats are typically viewed as messy or unattractive to users, and landscape architects and designers are often met with resistance when proposing such landscapes for public spaces. What visual elements can be used as communication tools by professionals in landscape architecture and ecological design to increase the understanding and appeal of pollinator spaces to the public? This knowledge could provide insight into the ways designers and landscape architects present their work to improve the chances of public approval, and thus implementation. A visual preference survey was implemented and became a vital strategy to find the relationship between key visual elements in images, and the visual appeal and the quality of habitat they communicate. Previous studies in the field of semiotics show that images contain visual elements of language that imply meaning through the use of signs and visual cues. Participants evaluated images showing naturalistic sites during the growing season, and showing subjects like flowers and pollinators, especially up-close images. The survey revealed various levels of understanding of ecological function in different demographics, and a proportional level of appeal. The relationships revealed from the survey were used to create a set of representation guidelines for landscape architects and designers to use when proposing urban pollinator habitat, and other urban ecological spaces. These tools will help to communicate the functionality and need of these spaces, while portraying their intrinsic beauty and potential for enjoyment. A conceptual design was produced from the literature to illustrate how the guidelines can be used in the context of an urban setting.
Keywords: Visual language; Photography; Semiotics; Ecological designPollinators